Persiapan Dinas Pariwisata Daerah Tingkat II Sleman dalam Menyambut Pariwisata 2005 dan Otonomi Daerah - Sri Larasati (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2004)
In the next 2005, RIPPNAS and WTO report that either foreign or domestic tourist is still coming to Indonesia, even move than 8,4 to 10 millions at the end of 2010. The declaration of municipal authority written in UU No. 22, 1999 conduct Yogyakarta tourism development, especially Sleman district. This research is done not only to know how far Sleman as the whole prepares in future but found that the government has already developed the tourism sector as well, such as putting down in RIPPDA, without neglecting the national, regional and economic life. Tourism's growing supported by natural, human resources and other side involve such as culture and business.